Comparative analysis of the ternary complex factors Elk-1, SAP-1a and SAP-2 (ERP/NET). - Price, M A (1995)
A transcription factor ternary complex composed of Serum Response Factor (SRF) and Ternary Complex Factor (TCF) mediates the response of the c-fos Serum Response Element (SRE) to growth factors and mitogens. Three Ets domain proteins, Elk-1, SAP-1 and ERP/NET, have been reported to have the properties of TCF. Here we compare Elk-1 and SAP-1a with the human ERP/NET homologue SAP-2. All three TCF RNAs are ubiquitously expressed at similar relative levels. All three proteins contain conserved regions that interact with SRF and the c-fos SRE with comparable efficiency, but in vitro complex formation by SAP-2 is strongly inhibited by its C-terminal sequences. Similarly, only Elk-1 and SAP-1a efficiently bind the c-fos SRE in vivo; ternary complex formation by SAP-2 is weak and is substantially unaffected by serum stimulation or v-ras co-expression. All three TCFs contain C-terminal transcriptional activation domains that are phosphorylated following growth factor stimulation. Activation requires conserved S/T-P motifs found in all the TCF family members. Each TCF activation domain can be phosphorylated in vitro by partially purified ERK2, and ERK activation in vivo is sufficient to potentiate transcriptional activation.